دور الخصائص المهنية والمهارات التدريسية في تطوير جودة الأداء التدريسي لدى معلمات القرآن الكريم بسلطنة عمان على ضوء احتياجاتهن التدريبية - Hilal Abdullah Ahmed Al-Sheibani
A descriptive study aimed at assessing training needs through analyzing the relationship between training needs and professional characteristics, teaching skills, and the quality of teaching performance among female teachers of the Noble Qur’an in the Sultanate of Oman. The study also aimed to reveal the potential effects of years of teaching, experience, and the number of training courses on training needs, professional characteristics, teaching skills, and quality of teaching performance. A representative sample of 249 female teachers was randomly selected from all 1264 female teachers of the Holy Quran in the Sultanate of Oman. The study used a questionnaire tool that was built based on previous studies. It included fifty items that represented the hypothetical formations (training needs, teaching skills, professional characteristics, and quality of teaching performance) in nine major dimensions: mastery in the subject matter of specialization, time management, administrative practice, scientific research, planning, communication skills, educational techniques, and evaluation methods. The objective characteristics of the study tools were confirmed by conceptual honesty, judge opinion, exploratory factor analysis, and the Karabakh alpha coefficient, which ranged between 0.983 and 0.98. It has indicated the validity of the tools for scientific research. To achieve the objectives of the study, the Standard Multiple Linear Regression, Multiple Variance Analysis, and two-way Variance Analysis were performed by the statistical package (SPSS). The results showed that training needs, professional characteristics, and teaching skills have an active role in explaining the quality of teaching performance. All dimensions except evaluation and scientific research contributed to the variable of training needs, scientific research with a variable of professional characteristics, and educational techniques with a variable of teaching skills. The Beta standard coefficient showed that the dimensions were descending according to their explanatory importance. Training needs ranged from weak to medium. The results also showed that there were no statistically significant differences for training needs, professional characteristics, and teaching skills depending on the variables of years of experience and the number of teaching courses. The results also showed that there are statistically significant differences in the quality of teaching performance, according to years of experience, for those with teaching experience from 5 to 10 years and those with teaching experience of more than 10 years. As for the number of training courses, it was in favor of female teachers who received 5 to 10 training courses. The study recommended that training needs should be taken into account in designing and implementing training programs for female teachers of the Holy Quran in the Sultanate of Oman based on the study conclusions.